Tempered glass sheet and its manufacturing method
Patent Information
- Application Number
- JP2020563298
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-10
- Filing Date
- 2019-12-24
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2039-12-24
Smart Images

Figure 0007651862000023 
Figure 0007651862000024 
Figure 0007651862000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a tempered glass sheet and a method for producing the same, and more particularly to a tempered glass sheet suitable for use as a cover glass for touch panel displays in mobile phones, digital cameras, PDAs (personal digital assistants) and the like, and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art Ion-exchanged reinforced glass sheets are used as cover glass for touch panel displays in applications such as mobile phones, digital cameras, and PDAs (personal digital assistants) (see Patent Document 1 and Non-Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-83045 A [Patent Document 2] Special Publication No. 2016-524581 [Patent Document 3] Special Publication No. 2011-510903 [Non-patent literature]
[0004] [Non-Patent Document 1] Tetsuro Izumiya et al., "New Glass and its Physical Properties", First Edition, Management Systems Research Institute, August 20, 1984, pp. 451-498 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0005] However, if a smartphone is accidentally dropped on the road, the cover glass may break, rendering the smartphone unusable. To avoid such a situation, it is important to increase the strength of the tempered glass plate.
[0006] Increasing the stress depth is an effective method for increasing the strength of tempered glass sheets. In more detail, when a smartphone falls and the cover glass collides with the road surface, protrusions and sand particles on the road surface penetrate the cover glass and reach the tensile stress layer, leading to breakage. Therefore, by increasing the stress depth of the compressive stress layer, it becomes difficult for protrusions and sand particles on the road surface to reach the tensile stress layer, making it possible to reduce the probability of breakage of the cover glass.
[0007] Lithium aluminosilicate glass is advantageous in obtaining a deep stress depth. In particular, when a glass plate to be tempered made of lithium aluminosilicate glass is immersed in a molten salt containing NaNO3 and Li ions in the glass are ion-exchanged with Na ions in the molten salt, a tempered glass plate having a deep stress depth can be obtained.
[0008] However, in conventional lithium aluminosilicate glass, the compressive stress value of the compressive stress layer may be too small. On the other hand, if the glass composition is designed to increase the compressive stress value of the compressive stress layer, the chemical stability may be reduced. Furthermore, lithium aluminosilicate glass is difficult to mold into a plate because the balance of the glass composition is lost and devitrification particles are easily generated during molding.
[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a strengthened glass sheet that can be formed into a plate shape, has excellent chemical stability, and is not easily broken when dropped. [Means for solving the problem]
[0010] As a result of various investigations, the inventors of the present invention have found that the above technical problems can be solved by restricting the glass composition to a predetermined range, and propose this as the present invention. That is, the tempered glass sheet of the present invention is a tempered glass having a compressive stress layer on its surface, and is characterized in that the glass composition contains, in mole %, 50-80% SiO2, 8-25% Al2O3, 0-10% B2O3, 3-15% Li2O, 3-21% Na2O, 0-10% K2O, 0-10% MgO, 0-10% ZnO, and 50-15% P2O.
[0011] In addition, the tempered glass plate of the present invention preferably satisfies the relationship of molar ratio ([Na2O]-[Li2O]) / ([Al2O3]+[B2O3]+[P2O5])≦0.29. Here, [Na2O] refers to the molar % content of Na2O. [Li2O] refers to the molar % content of Li2O. [Al2O3] refers to the molar % content of Al2O3. [B2O3] refers to the molar % content of B2O3. [P2O5] refers to the molar % content of P2O5. ([Na2O]-[Li2O]) / ([Al2O3]+[B2O3]+[P2O5]) refers to the amount obtained by subtracting the Li2O content from the Na2O content, divided by the total amount of Al2O3, B2O3, and P2O5.
[0012] The tempered glass plate of the present invention preferably satisfies the relationship of molar ratio ([B2O3]+[Na2O]-[P2O5]) / ([Al2O3]+[Li2O])≧0.30, where ([B2O3]+[Na2O]-[P2O5]) / ([Al2O3]+[Li2O]) refers to the value obtained by subtracting the content of P2O5 from the total amount of B2O3 and Na2O, and dividing the result by the total amount of Al2O3 and Li2O.
[0013] The tempered glass plate of the present invention is characterized in that it contains 12 mol% or more of ([Li2O]+[Na2O]+[K2O]) and satisfies the relationship of [SiO2]+1.2×[P2O5]-3×[Al2O3]-2×[Li2O]-1.5×[Na2O]-[K2O]-[B2O3]≧-22 mol%. Here, [K2O] refers to the mol% content of K2O. [SiO2] refers to the mol% content of SiO2. ([Li2O]+[Na2O]+[K2O]) refers to the total amount of Li2O, Na2O and K2O. [SiO2] + 1.2 × [P2O5] - 3 × [Al2O3] - 2 × [Li2O] - 1.5 × [Na2O] - [K2O] - [B2O3] refers to the sum of the SiO2 content and 1.2 times the P2O5 content minus 3 times the Al2O3 content, 2 times the Li2O content, 1.5 times the Na2O content, K2O content, and B2O3 content.
[0014] In addition, the tempered glass plate of the present invention preferably has a P2O5 content of 0.1 to 2.3 mol %.
[0015] In addition, the tempered glass plate of the present invention preferably has a B2O3 content of 0.1 to 4 mol %.
[0016] In addition, in the tempered glass plate of the present invention, the compressive stress value of the outermost surface of the compressive stress layer is preferably 200 to 1000 MPa. Here, the "compressive stress value of the outermost surface" and the "stress depth" refer to values measured from a phase difference distribution curve observed using, for example, a scattered light photoelastic stress meter SLP-1000 (manufactured by Orihara Manufacturing Co., Ltd.). The stress depth refers to the depth at which the stress value becomes zero. In addition, in calculating the stress characteristics, the refractive index of each measurement sample is 1.51, and the optical elastic constant is 30.1 [(nm / cm) / MPa].
[0017] In the tempered glass plate of the present invention, the stress depth of the compressive stress layer is preferably 50 to 200 μm.
[0018] In addition, in the tempered glass sheet of the present invention, the high-temperature viscosity is 10 2.5It is preferable that the temperature at which the viscosity of the polymer is 10 dPa·s is less than 1650°C. 2.5 The "temperature at dPa·s" can be measured, for example, by the platinum sphere pulling method.
[0019] The tempered glass sheet of the present invention preferably has an overflow joining surface at the center in the sheet thickness direction, that is, is formed by an overflow downdraw method. Here, the "overflow downdraw method" is a method for producing a glass sheet by making molten glass overflow from both sides of a refractory molding and drawing the overflowing molten glass downward while joining at the lower end of the refractory molding.
[0020] The tempered glass plate of the present invention is preferably used as a cover glass for a touch panel display.
[0021] The tempered glass sheet of the present invention is characterized in that the tempered glass having a compressive stress layer on the surface contains 17 mol% or more of Al2O3, 1 mol% or more of P2O5, and 12 mol% or more of ([Li2O]+[Na2O]+[K2O]), and satisfies the relationship [SiO2]+1.2×[P2O5]-3×[Al2O3]-2×[Li2O]-1.5×[Na2O]-[K2O]-[B2O3]≧-22 mol%. This makes it easier to obtain glass that can be formed into a plate shape while improving ion exchange performance and has high acid resistance.
[0022] In addition, the tempered glass plate of the present invention preferably has an Fe2O3 content of 0.001 to 0.1 mol %.
[0023] In addition, the tempered glass plate of the present invention preferably has a TiO2 content of 0.001 to 0.1 mol %.
[0024] In addition, the tempered glass plate of the present invention preferably has an SnO2 content of 0.01 to 1 mol %.
[0025] The tempered glass plate of the present invention preferably has a Cl content of 0.001 to 0.1 mol %.
[0026] The tempered glass sheet of the present invention preferably has a stress profile in the thickness direction that has at least a first peak, a second peak, a first bottom, and a second bottom.
[0027] The glass plate to be tempered of the present invention is characterized in that it has a glass composition containing, in mole percent, 50-80% SiO2, 8-25% Al2O3, 0-10% B2O3, 3-15% Li2O, 3-21% Na2O, 0-10% K2O, 0-10% MgO, 0-10% ZnO, and 50-15% P2O.
[0028] The method for producing a tempered glass plate of the present invention is characterized by comprising: a preparation step of preparing a glass plate to be tempered containing, in mol %, 50-80% SiO2, 8-25% Al2O3, 0-10% B2O3, 3-15% Li2O, 3-21% Na2O, 0-10% K2O, 0-10% MgO, 0-10% ZnO, and 50-15% P2O; and an ion exchange step of performing ion exchange treatment on the glass plate to be tempered multiple times to obtain a tempered glass plate having a compressive stress layer on a surface thereof. [Brief description of the drawings]
[0029] [Figure 1] FIG. 2 is an explanatory diagram illustrating a stress profile having a first peak, a second peak, a first bottom, and a second bottom. [Diagram 2] FIG. 11 is another explanatory diagram illustrating a stress profile having a first peak, a second peak, a first bottom, and a second bottom. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The tempered glass plate (glass plate to be tempered) of the present invention contains, in mole percent, 50-80% SiO2, 8-25% Al2O3, 0-10% B2O3, 3-15% Li2O, 3-21% Na2O, 0-10% K2O, 0-10% MgO, 0-10% ZnO, and 50-15% P2O as a glass composition. The reasons for limiting the content range of each component are as follows. In the explanation of the content range of each component, % indicates mol % unless otherwise specified.
[0031] SiO2 is a component that forms a glass network. If the content of SiO2 is too low, vitrification becomes difficult, and the thermal expansion coefficient becomes too high, so that the thermal shock resistance is easily reduced. Therefore, the preferred lower limit range of SiO2 is 50% or more, 55% or more, 57% or more, 59% or more, and particularly 61% or more. On the other hand, if the content of SiO2 is too high, the melting property and moldability are easily reduced, and the thermal expansion coefficient becomes too low, so that it is difficult to match the thermal expansion coefficient of the surrounding material. Therefore, the preferred upper limit range of SiO2 is 80% or less, 70% or less, 68% or less, 66% or less, 65% or less, and particularly 64.5% or less.
[0032] Al2O3 is a component that enhances ion exchange performance, and also enhances strain point, Young's modulus, fracture toughness, and Vickers hardness. Therefore, the preferred lower limit range of Al2O3 is 8% or more, 10% or more, 12% or more, 13% or more, 14% or more, 14.4% or more, 15% or more, 15.3% or more, 15.6% or more, 16% or more, 16.5% or more, 17% or more, 17.2% or more, 17.5% or more, 17.8% or more, 18% or more, more than 18%, 18.3% or more, particularly 18.5% or more, 18.6% or more, 18.7% or more, and 18.8% or more. On the other hand, if the content of Al2O3 is too high, the high-temperature viscosity increases, and melting property and formability tend to decrease. In addition, devitrification crystals tend to precipitate in the glass, making it difficult to form it into a plate shape by the overflow downdraw method or the like. In particular, when an alumina-based refractory is used as the molded refractory and formed into a plate shape by the overflow down-draw method, devitrified crystals of spinel are likely to precipitate at the interface with the alumina-based refractory. Furthermore, acid resistance is also reduced, making it difficult to apply to the acid treatment process. Therefore, the preferred upper limit range of Al2O3 is 25% or less, 21% or less, 20.5% or less, 20% or less, 19.9% or less, 19.5% or less, 19.0% or less, particularly 18.9% or less. If the content of Al2O3, which has a large effect on ion exchange performance, is set within a preferred range, it becomes easy to form a profile having a first peak, a second peak, a first bottom, and a second bottom.
[0033] B2O3 is a component that reduces the high-temperature viscosity and density, stabilizes the glass, makes it difficult for crystals to precipitate, and lowers the liquidus temperature. If the B2O3 content is too low, the stress depth in the ion exchange between the Li ions in the glass and the Na ions in the molten salt becomes too deep, resulting in a compressive stress value (CS Na ) tends to become smaller. In addition, the glass may become unstable, and devitrification resistance may decrease. Therefore, the preferable lower limit range of B2O3 is 0% or more, 0.1% or more, 0.2% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, 0.9% or more, and particularly 1% or more. On the other hand, if the content of B2O3 is too high, there is a risk that the stress depth may become shallow. In particular, the efficiency of ion exchange between Na ions contained in the glass and K ions in the molten salt is likely to decrease, and the stress depth (DOL_ZEROK ) tends to become small. Therefore, the preferred upper limit range of B2O3 is 10% or less, 5% or less, 4% or less, 3.8% or less, 3.5% or less, 3.3% or less, 3.2% or less, 3.1% or less, 3% or less, particularly 2.9% or less. If the B2O3 content is within the preferred range, it becomes easier to form a profile having a first peak, a second peak, a first bottom, and a second bottom.
[0034] Li2O is an ion-exchange component, and is an essential component for obtaining a deep stress depth by ion-exchanging Li ions contained in the glass with Na ions in the molten salt. Li2O is also a component that reduces high-temperature viscosity and improves meltability and formability, as well as increasing Young's modulus. Therefore, the preferred lower limit range of Li2O is 3% or more, 4% or more, 5% or more, 5.5% or more, 6.5% or more, 7% or more, 7.3% or more, 7.5% or more, 7.8% or more, and particularly 8% or more. Therefore, the preferred upper limit range of Li2O is 15% or less, 13% or less, 12% or less, 11.5% or less, 11% or less, 10.5% or less, less than 10%, and particularly 9.9% or less, 9% or less, and 8.9% or less.
[0035] Na2O is an ion exchange component, and is a component that reduces high-temperature viscosity and improves melting and moldability. Na2O is also a component that improves devitrification resistance, and is particularly a component that suppresses devitrification caused by reaction with alumina-based refractories. Therefore, the preferred lower limit range of Na2O is 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 7.5% or more, 8% or more, 8.5% or more, 8.8% or more, and particularly 9% or more. On the other hand, if the content of Na2O is too high, the thermal expansion coefficient becomes too high and the thermal shock resistance is easily reduced. In addition, the component balance of the glass composition may be lost, and the devitrification resistance may be reduced instead. Therefore, the preferred upper limit range of Na2O is 21% or less, 20% or less, 19% or less, particularly 18% or less, 15% or less, 13% or less, 11% or less, and particularly 10% or less.
[0036] K2O is a component that reduces high-temperature viscosity and improves melting and moldability. However, if the content of K2O is too high, the thermal expansion coefficient becomes too high, and the thermal shock resistance is likely to decrease. In addition, the compressive stress value of the outermost surface is likely to decrease. Therefore, the preferred upper limit range of K2O is 10% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1.5% or less, 1% or less, less than 1%, 0.5% or less, and particularly less than 0.1%. In addition, from the viewpoint of deepening the stress depth, the preferred lower limit range of K2O is 0% or more, 0.1% or more, 0.3% or more, and particularly 0.5% or more.
[0037] The molar ratio [Li2O] / ([Na2O]+[K2O]) is preferably 0.4 to 1.0, 0.5 to 0.9, and particularly 0.6 to 0.8. If the molar ratio [Li2O] / ([Na2O]+[K2O]) is too small, there is a risk that the ion exchange performance cannot be fully exhibited. In particular, the efficiency of ion exchange between the Li ions contained in the glass and the Na ions in the molten salt is likely to decrease. On the other hand, if the molar ratio [Li2O] / ([Na2O]+[K2O]) is too large, devitrified crystals are likely to precipitate in the glass, making it difficult to form the glass into a plate shape by the overflow downdraw method or the like. Note that "[Li2O] / ([Na2O]+[K2O])" refers to the value obtained by dividing the content of Li2O by the combined amount of Na2O and K2O.
[0038] MgO is a component that reduces high-temperature viscosity, improves melting property and moldability, and increases strain point and Vickers hardness. Among alkaline earth metal oxides, MgO is a component that has a large effect of improving ion exchange performance. However, if the content of MgO is too high, devitrification resistance is likely to decrease, and it becomes difficult to suppress devitrification caused by reaction with alumina-based refractories in particular. Therefore, the preferred content of MgO is 0 to 10%, 0 to 5%, 0.1 to 4%, 0.2 to 3.5%, and particularly less than 0.5 to 3%.
[0039] ZnO is a component that enhances ion exchange performance, and is particularly effective in increasing the compressive stress value of the outermost surface. It is also a component that reduces high-temperature viscosity without reducing low-temperature viscosity. The preferred lower limit range of ZnO is 0% or more, 0.1% or more, 0.3% or more, 0.5% or more, 0.7% or more, and particularly 1% or more. On the other hand, if the ZnO content is too high, the glass tends to undergo phase separation, the devitrification resistance tends to decrease, the density tends to increase, and the stress depth tends to become shallow. Therefore, the preferred upper limit range of ZnO is 10% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1.5% or less, 1.3% or less, 1.2% or less, and particularly 1.1% or less.
[0040] P2O5 is a component that enhances ion exchange performance, and in particular deepens the stress depth. It also improves acid resistance. If the P2O5 content is too low, there is a risk that the ion exchange performance will not be fully demonstrated. In particular, the efficiency of ion exchange between the Na ions contained in the glass and the K ions in the molten salt is likely to decrease, and the stress depth of the compressive stress layer (DOL_ZERO K ) tends to become small. In addition, the glass may become unstable, and the devitrification resistance may decrease. Therefore, the preferable lower limit range of P2O5 is 0% or more, 0.1% or more, 0.4% or more, 0.7% or more, 1% or more, 1.2% or more, 1.4% or more, 1.6% or more, 2% or more, 2.3% or more, 2.5% or more, and particularly 3% or more. On the other hand, if the content of P2O5 is too high, the glass tends to undergo phase separation and the water resistance tends to decrease. In addition, the stress depth in the ion exchange between the Li ions contained in the glass and the Na ions in the molten salt becomes too deep, and as a result, the compressive stress value (CS Na ) tends to become smaller. Therefore, the preferable upper limit range of P2O5 is 15% or less, 10% or less, 5% or less, 4.5% or less, and 4% or less. If the content of P2O5 is within the preferable range, it becomes easier to form a non-monotonic profile.
[0041] Alkali metal oxides are ion exchange components that reduce high-temperature viscosity and improve melting and moldability. If the content of alkali metal oxides ([Li2O]+[Na2O]+[K2O]) is too high, the thermal expansion coefficient may increase. Also, acid resistance may decrease. Therefore, the preferred lower limit range of alkali metal oxides ([Li2O]+[Na2O]+[K2O]) is 10% or more, 11% or more, 12% or more, 13% or more, 14% or more, or 15% or more. Therefore, the preferred upper limit range of alkali metal oxides ([Li2O]+[Na2O]+[K2O]) is 25% or less, 23% or less, 20% or less, 19% or less, or 18% or less.
[0042] The molar ratio [Li2O] / [P2O5] is preferably 4 to 30, 10 to 25, and particularly 15 to 20. If the molar ratio [Li2O] / [P2O5] is too small, the efficiency of ion exchange between the Li ions contained in the glass and the Na ions in the molten salt is likely to decrease. On the other hand, if the molar ratio [Li2O] / [P2O5] is too large, devitrified crystals are likely to precipitate in the glass, making it difficult to form the glass into a plate shape by the overflow downdraw method or the like. Here, "[Li2O] / [P2O5]" refers to the value obtained by dividing the content of Li2O by the content of P2O5.
[0043] The molar ratio ([Na2O]-[Li2O]) / ([Al2O3]+[B2O3]+[P2O5]) is preferably 0.29 or less, 0.27 or less, 0.26 or less, 0.25 or less, 0.23 or less, 0.20 or less, and particularly ...3 or less, 0.23 or less, 0.20 or less, and particularly preferably 0.23 or less, 0.23 or less, 0.23 or less, 0.20 or less, and 0.15 or less If the molar ratio ([Na2O]-[Li2O]) / ([Al2O3]+[B2O3]+[P2O5]) is too large, there is a risk that the ion exchange performance will not be fully demonstrated. In particular, the efficiency of ion exchange between the Li ions contained in the glass and the Na ions in the molten salt is likely to decrease.
[0044] The molar ratio ([B2O3]+[Na2O]-[P2O5]) / ([Al2O3]+[Li2O]) is preferably 0.30 or more, 0.35 or more, 0.40 or more, 0.42 or more, 0.43 or more, particularly preferably 0.45 or more. EndIf the molar ratio ([B2O3] + [Na2O] - [P2O5]) / ([Al2O3] + [Li2O]) is too small, devitrified crystals tend to precipitate in the glass, making it difficult to form it into a plate shape by the overflow downdraw method or the like.
[0045] ([SiO2]+1.2×[P2O5]-3×[Al2O3]-2×[Li2O]-1.5×[Na2O]-[K2O]-[B2O3]) is preferably at least -40%, at least -30%, at least -25%, at least -24%, at least -23%, at least -22%, at least -21%, at least -20%, at least -19%, and particularly at least -18%. If ([SiO2]+1.2×[P2O5]-3×[Al2O3]-2×[Li2O]-1.5×[Na2O]-[K2O]-[B2O3]) is too small, the acid resistance is easily reduced. On the other hand, if ([SiO2]+1.2×[P2O5]-3×[Al2O3]-2×[Li2O]-1.5×[Na2O]-[K2O]-[B2O3]) is too large, there is a risk that the ion exchange performance cannot be fully exhibited. Therefore, ([SiO2]+1.2×[P2O5]-3×[Al2O3]-2×[Li2O]-1.5×[Na2O]-[K2O]-[B2O3]) is preferably 30 mol% or less, 20 mol% or less, 15 mol% or less, 10 mol% or less, 5 mol% or less, and particularly 0 mol% or less.
[0046] In addition to the above components, the following components may be added:
[0047] Compared with other components, CaO is a component that reduces high-temperature viscosity, improves meltability and moldability, and increases strain point and Vickers hardness without reducing devitrification resistance. However, if the CaO content is too high, there is a risk that the ion exchange performance will decrease and the ion exchange solution will deteriorate during ion exchange treatment. Therefore, the preferred upper limit range of CaO is 6% or less, 5% or less, 4% or less, 3.5% or less, 3% or less, 2% or less, 1% or less, less than 1%, 0.5% or less, and particularly less than 0.1%.
[0048] SrO and BaO are components that reduce high-temperature viscosity, improve meltability and formability, and increase strain point and Young's modulus, but if their contents are too high, the ion exchange reaction is likely to be inhibited, and the density and thermal expansion coefficient become unduly high and the glass is likely to devitrify. Therefore, the preferred contents of SrO and BaO are 0 to 2%, 0 to 1.5%, 0 to 1%, 0 to 0.5%, and 0 to 0.1%, respectively, and particularly 0 to less than 0.1%.
[0049] ZrO2 is a component that increases the Vickers hardness and also increases the viscosity near the liquidus viscosity and the strain point, but if the content is too high, there is a risk that the devitrification resistance will be significantly reduced. Therefore, the preferred content of ZrO2 is 0 to 3%, 0 to 1.5%, 0 to 1%, and particularly 0 to 0.1%.
[0050] TiO2 is a component that enhances ion exchange performance and also reduces high-temperature viscosity, but if the content is too high, transparency and devitrification resistance tend to decrease. Therefore, the preferred content of TiO2 is 0 to 3%, 0 to 1.5%, 0 to 1%, 0 to 0.1%, and particularly 0.001 to 0.1 mol%.
[0051] SnO2 is a component that enhances ion exchange performance, but if the content is too high, devitrification resistance is likely to decrease. Therefore, the lower limit of SnO2 is preferably 0.005% or more, 0.01% or more, and particularly preferably 0.1% or more, and the upper limit is preferably 3% or less, 2% or less, and particularly preferably 1% or less.
[0052] Cl is a fining agent, but if its content is too high, it is a component that has a negative effect on the environment and equipment. Therefore, the preferred lower limit of Cl is 0.001% or more, particularly 0.01% or more, and the preferred upper limit is 0.3% or less, 0.2% or less, particularly 0.1% or less.
[0053] As a fining agent, one or more selected from the group consisting of SO3 and CeO2 (preferably the group consisting of SO3) may be added in an amount of 0.001 to 1%.
[0054] Fe2O3 is an impurity that is inevitably mixed in from the raw materials. The preferred content of Fe2O3 is less than 1000 ppm (less than 0.1%), less than 800 ppm, less than 600 ppm, less than 400 ppm, and particularly less than 300 ppm. If the content of Fe2O3 is too high, the transmittance of the cover glass is likely to decrease. On the other hand, the lower limit range is 10 ppm or more, 20 ppm or more, 30 ppm or more, 50 ppm or more, 80 ppm or more, or 100 ppm or more. If the Fe2O3 content is too low, high purity raw materials are used, which increases the raw material cost and makes it impossible to manufacture the product at low cost.
[0055] teeth, Rare earth oxides such as Nd2O3, La2O3, Y2O3, Nb2O5, Ta2O5, and Hf2O3 are components that increase the Young's modulus. However, the raw material cost is high, and if added in large amounts, the devitrification resistance is likely to decrease. Therefore, the preferable content of rare earth oxides is 5% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, and particularly 0.1% or less.
[0056] From an environmental perspective, the tempered glass plate (glass plate to be tempered) of the present invention preferably does not substantially contain As2O3, Sb2O3, PbO, or F as a glass composition. From an environmental perspective, it is also preferable that the glass does not substantially contain Bi2O3. The phrase "substantially does not contain ..." means that the specified components are not actively added as glass components, but the addition of impurity levels is permitted, and specifically refers to the case where the content of the specified components is less than 0.05%.
[0057] The tempered glass plate (glass plate to be tempered) of the present invention preferably has the following properties.
[0058] The density is preferably 2.55 g / cm 3 Below, 2.53g / cm 3 Below 2.50g / cm 3 Below, 2.49g / cm 3 Below, 2.45g / cm 3 The following, especially 2.35 to 2.44 g / cm 3The lower the density, the lighter the tempered glass sheet can be.
[0059] The thermal expansion coefficient at 30 to 380°C is preferably 150×10 -7 / ℃ or less, 100×10 -7 / ℃ or less, especially 50~95×10 -7 / ° C. Note that the "thermal expansion coefficient at 30 to 380° C." refers to the average thermal expansion coefficient measured using a dilatometer.
[0060] The softening point is preferably 950° C. or less, 930° C. or less, 900° C. or less, 880° C. or less, or 860° C. or less, particularly 850 to 700° C. The "softening point" refers to a value measured based on the method of ASTM C338.
[0061] High temperature viscosity 10 2.5 The temperature at dPa·s is preferably 1660° C. or less, less than 1620° C., 1600° C. or less, and particularly preferably 1400 to 1590° C. 2.5 If the temperature at dPa·s is too high, the melting property and formability decrease, making it difficult to form the molten glass into a sheet. 2.5 "Temperature at dPa·s" refers to the value measured by the platinum ball pulling method.
[0062] The liquidus viscosity is preferably 10 3.74 dPa s or more, 10 4.5 dPa s or more, 10 4.8 dPa s or more, 10 4.9 dPa s or more, 10 5.0 dPa s or more, 10 5.1 dPa s or more, 10 5.2 dPa s or more, 10 5.3 dPa s or more, 10 5.4 dPa s or more, especially 10 5.5It is dPa·s or more. The higher the liquidus viscosity, the better the resistance to devitrification and the less likely devitrification particles will occur during molding. Here, "liquidus viscosity" refers to the value of the viscosity at the liquidus temperature measured using the platinum ball pull-up method. "Liquidus temperature" is the highest temperature at which devitrification (devitrification particles) is observed inside the glass when glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains on the 50 mesh (300 μm) is placed in a platinum boat and held in a temperature gradient furnace for 24 hours, after which the platinum boat is removed and observed under a microscope.
[0063] The Young's modulus is preferably 70 GPa or more, 74 GPa or more, 75 to 100 GPa, particularly 76 to 90 GPa. If the Young's modulus is low, the cover glass is likely to bend when the plate thickness is thin. The "Young's modulus" can be calculated by the well-known resonance method.
[0064] The tempered glass plate of the present invention has a compressive stress layer on the surface. The compressive stress value of the outermost surface is preferably 165 MPa or more, 200 MPa or more, 220 MPa or more, 250 MPa or more, 280 MPa or more, 300 MPa or more, 310 MPa or more, particularly 320 MPa or more. The larger the compressive stress value of the outermost surface, the higher the Vickers hardness. On the other hand, if an extremely large compressive stress is formed on the surface, the tensile stress inherent in the tempered glass becomes extremely high, and there is a risk that the dimensional change before and after the ion exchange treatment becomes large. For this reason, the compressive stress value of the outermost surface is preferably 1000 MPa or less, 900 MPa or less, 700 MPa or less, 680 MPa or less, 650 MPa or less, particularly 600 MPa or less. In addition, if the ion exchange time is shortened or the temperature of the ion exchange solution is lowered, the compressive stress value of the outermost surface tends to increase.
[0065] The stress depth is preferably 50 μm or more, 60 μm or more, 80 μm or more, 100 μm or more, particularly 120 μm or more. The deeper the stress depth, the more difficult it becomes for protrusions and sand particles on the road surface to reach the tensile stress layer when the smartphone is dropped, making it possible to reduce the probability of breakage of the cover glass. On the other hand, if the stress depth is too deep, there is a risk that the dimensional change before and after the ion exchange treatment will be large. Furthermore, the compressive stress value of the outermost surface tends to decrease. Therefore, the stress depth is preferably 200 μm or less, 180 μm or less, 150 μm or less, particularly 140 μm or less. In addition, if the ion exchange time is extended or the temperature of the ion exchange solution is increased, the stress depth tends to become deeper.
[0066] In the tempered glass plate of the present invention, the plate thickness is preferably 2.0 mm or less, 1.5 mm or less, 1.3 mm or less, 1.1 mm or less, 1.0 mm or less, 0.9 mm or less, particularly 0.8 mm or less. The smaller the plate thickness, the lower the mass of the tempered glass plate. On the other hand, if the plate thickness is too thin, it is difficult to obtain the desired mechanical strength. Therefore, the plate thickness is preferably 0.3 mm or more, 0.4 mm or more, 0.5 mm or more, 0.6 mm or more, particularly 0.7 mm or more.
[0067] The method for producing a tempered glass sheet of the present invention is characterized by comprising a preparation step of preparing a glass sheet to be tempered containing, in mole percent, 50-80% SiO2, 8-25% Al2O3, 0-10% B2O3, 3-15% Li2O, 3-21% Na2O, 0-10% K2O, 0-10% MgO, 0-10% ZnO, and 50-15% P2O, and an ion exchange step of subjecting the glass sheet to be tempered to an ion exchange treatment multiple times to obtain a tempered glass sheet having a compressive stress layer on its surface. Note that, although the method for producing a tempered glass sheet of the present invention is characterized by performing an ion exchange treatment multiple times, the tempered glass sheet of the present invention includes not only a case where the ion exchange treatment is performed multiple times, but also a case where the ion exchange treatment is performed only once.
[0068] The method for producing tempered glass is, for example, as follows. First, glass raw materials prepared to obtain a desired glass composition are charged into a continuous melting furnace, heated and melted at 1400 to 1700°C, and then clarified. The molten glass is then fed to a forming device, formed into a plate, and cooled. After forming into a plate, a known method can be used to cut the glass into a predetermined size.
[0069] As a method for forming molten glass into a plate, the overflow down-draw method is preferred. In the overflow down-draw method, the surface to be the glass plate is not in contact with the surface of the molded refractory, and is formed into a plate in a free surface state. Therefore, a glass plate having good surface quality can be produced inexpensively even though it is unpolished. Furthermore, in the overflow down-draw method, an alumina-based refractory or a zirconia-based refractory is used as the molded refractory. And, the tempered glass plate (glass plate to be tempered) of the present invention has good compatibility with alumina-based refractories and zirconia-based refractories (particularly alumina-based refractories), and therefore has a property of being unlikely to react with these refractories to generate bubbles, bumps, etc.
[0070] In addition to the overflow downdraw method, various other forming methods can be used, such as the float method, the downdraw method (slot downdraw method, redraw method, etc.), the roll-out method, and the press method.
[0071] During the forming of the molten glass, it is preferable to cool the temperature range between the annealing point and the strain point of the molten glass at a cooling rate of 3°C / min or more and less than 1000°C / min, and the lower limit of the cooling rate is preferably 10°C / min or more, 20°C / min or more, 30°C / min or more, particularly 50°C / min or more, and the upper limit is preferably less than 1000°C / min, less than 500°C / min, particularly less than 300°C / min. If the cooling rate is too fast, the glass structure becomes coarse, making it difficult to increase the Vickers hardness after the ion exchange treatment. On the other hand, if the cooling rate is too slow, the production efficiency of the glass sheet decreases.
[0072] In the method for producing a tempered glass sheet of the present invention, multiple ion exchange treatments are performed. As the multiple ion exchange treatments, it is preferable to perform an ion exchange treatment of immersion in a molten salt containing KNO3 molten salt, and then an ion exchange treatment of immersion in a molten salt containing NaNO3 molten salt. In this way, the compressive stress value of the outermost surface can be increased while ensuring a deep stress depth.
[0073] In particular, in the manufacturing method of the tempered glass sheet of the present invention, it is preferable to perform an ion exchange process (first ion exchange process) in which the glass is immersed in a NaNO3 molten salt or a mixed molten salt of NaNO3 and KNO3, and then perform an ion exchange process (second ion exchange process) in which the glass is immersed in a mixed molten salt of KNO3 and LiNO3. In this way, it is possible to form a non-monotonic stress profile as shown in Figures 1 and 2, that is, a stress profile having at least a first peak, a second peak, a first bottom, and a second bottom. As a result, it is possible to significantly reduce the probability of breakage of the cover glass when the smartphone is dropped.
[0074] In the first ion exchange process, Li ions contained in the glass and Na ions in the molten salt undergo ion exchange, and when a mixed molten salt of NaNO3 and KNO3 is used, Na ions contained in the glass and K ions in the molten salt also undergo ion exchange. Here, the ion exchange between Li ions contained in the glass and Na ions in the molten salt is faster than that between Na ions contained in the glass and K ions in the molten salt, and the ion exchange efficiency is higher. In the second ion exchange process, Na ions in the vicinity of the glass surface (shallow region from the outermost surface to 20% of the plate thickness) and Li ions in the molten salt undergo ion exchange, and in addition, Na ions in the vicinity of the glass surface (shallow region from the outermost surface to 20% of the plate thickness) and K ions in the molten salt undergo ion exchange. That is, in the second ion exchange process, K ions with a large ionic radius can be introduced while removing Na ions in the vicinity of the glass surface. As a result, the compressive stress value of the outermost surface can be increased while maintaining a deep stress depth.
[0075] In the first ion exchange step, the temperature of the molten salt is preferably 360 to 400° C., and the ion exchange time is preferably 30 minutes to 6 hours. In the second ion exchange step, the temperature of the ion exchange solution is preferably 370 to 400° C., and the ion exchange time is preferably 15 minutes to 3 hours.
[0076] In order to form a non-monotonic stress profile, it is preferable that the NaNO3 concentration is higher than the KNO3 concentration in the mixed molten salt of NaNO3 and KNO3 used in the first ion exchange process, and it is preferable that the KNO3 concentration is higher than the LiNO3 concentration in the mixed molten salt of KNO3 and LiNO3 used in the second ion exchange process.
[0077] In the mixed molten salt of NaNO3 and KNO3 used in the first ion exchange step, the concentration of KNO3 is preferably 0 mass% or more, 0.5 mass% or more, 1 mass% or more, 5 mass% or more, 7 mass% or more, 10 mass% or more, 15 mass% or more, particularly 20 to 90 mass%. If the concentration of KNO3 is too high, there is a risk that the compressive stress value formed when Li ions contained in the glass and Na ions in the molten salt are ion-exchanged is too low. Also, if the concentration of KNO3 is too low, there is a risk that it becomes difficult to measure the stress using the surface stress meter FSM-6000.
[0078] In the mixed molten salt of KNO3 and LiNO3 used in the second ion exchange step, the LiNO3 concentration is preferably from 0 to 5 mass%, from 0 to 3 mass%, from 0 to 2 mass%, and particularly from 0.1 to 1 mass%. If the LiNO3 concentration is too low, Na ions near the glass surface are difficult to remove. On the other hand, if the LiNO3 concentration is too high, there is a risk that the compressive stress value formed by ion exchange between Na ions near the glass surface and K ions in the molten salt may be too low. EXAMPLES
[0079] The present invention will be described below based on examples. Note that the following examples are merely illustrative and the present invention is not limited to the following examples.
[0080] Tables 1 to 22 show the glass compositions and glass properties of the examples of the present invention (samples Nos. 1 to 35 and 38 to 215) and comparative examples (samples Nos. 36 and 37). In the tables, "NA" means not measured, and "(Na-Li) / (Al+B+P)" is the molar ratio ([NaO] - [Li2O]) / ([Al2O3]+[B2O3]+[P2O5]), and "(B+Na-P) / (Al+Li)" is the molar ratio ([B2O3]+[Na2O] - [P2O5]) / ([Al2O3]+[Li2O]), and "Si+1.2P-3Al-2Li-1.5Na-KB" means [SiO2]+1.2×[P2O5]-3×[Al2O3]-2×[Li2O]-1.5×[Na2O]-[K2O]-[B2O3].
[0081] [Table 1]
[0082] [Table 2]
[0083] [Table 3]
[0084] [Table 4]
[0085] [Table 5]
[0086] [Table 6]
[0087] [Table 7]
[0088]
Table 8
[0089]
Table 9
[0090]
Table 10
[0091]
Table 11
[0092]
Table 12
[0093]
Table 13
[0094]
Table 14
[0095]
Table 15
[0096]
Table 16
[0097]
Table 17
[0098] [Table 18]
[0099] [Table 19]
[0100] [Table 20]
[0101] [Table 21]
[0102] [Table 22]
[0103] Each sample in the table was prepared as follows. First, glass raw materials were mixed to obtain the glass composition in the table, and melted at 1600°C for 21 hours using a platinum pot. The resulting molten glass was then poured onto a carbon plate and formed into a flat plate shape, after which it was cooled at 3°C / min in the temperature range between the annealing point and the strain point to obtain a glass plate (glass plate to be strengthened). The surface of the obtained glass plate was optically polished to a plate thickness of 1.5 mm, and various properties were evaluated.
[0104] The density (ρ) is a value measured by the well-known Archimedes method.
[0105] Thermal expansion coefficient (α 30-380℃ ) is the average thermal expansion coefficient measured using a dilatometer.
[0106] High temperature viscosity 10 2.5 Temperature in dPa s (10 2.5 dPa·s) is a value measured by the platinum ball pulling method.
[0107] The softening point (Ts) is a value measured based on the method of ASTM C338.
[0108] The liquidus temperature (TL) was determined by placing the glass powder that passed through a standard sieve of 30 mesh (500 μm) and remained on the 50 mesh (300 μm) in a platinum boat, holding it in a temperature gradient furnace for 24 hours, then removing the platinum boat and observing it under a microscope, at which devitrification (devitrification particles) was observed inside the glass. The liquidus viscosity (log η at TL) is the value of the viscosity at the liquidus temperature measured by the platinum ball pulling method, and is expressed as log η by taking the logarithm.
[0109] The Young's modulus (E) was calculated according to JIS R1602-1995 "Testing method for elastic modulus of fine ceramics."
[0110] The acid resistance test was carried out by using glass samples with dimensions of 50 x 10 x 1.0 mm, mirror-polished on both sides, as measurement samples. After thorough cleaning with neutral detergent and pure water, the samples were immersed in a 5% by mass HCl aqueous solution heated to 80°C for 24 hours, and the mass loss per unit surface area (mg / cm2) before and after immersion was measured. 2 ) was calculated.
[0111] The alkali resistance test used glass samples with dimensions of 50 x 10 x 1.0 mm, mirror-polished on both sides, as measurement samples. After thorough cleaning with neutral detergent and pure water, the samples were immersed in a 5% by mass NaOH aqueous solution heated to 80°C for 6 hours, and the mass loss per unit surface area (mg / cm2) before and after immersion was measured. 2 ) was calculated.
[0112] Next, each glass plate was immersed in molten KNO3 salt at 430°C for 4 hours to carry out an ion exchange treatment, obtaining a tempered glass plate with a compressive stress layer on the surface. The glass surface was then cleaned, and the compressive stress value (CS K ) and stress depth (DOL_ZEROK ) was calculated. Here, DOL_ZERO K is the depth at which the compressive stress value becomes zero. In calculating the stress characteristics, the refractive index of each sample was set to 1.51 and the optical elastic constant was set to 30.1 [(nm / cm) / MPa].
[0113] In addition, each glass plate was immersed in molten NaNO3 salt at 380°C for 1 hour to carry out an ion exchange treatment to obtain a tempered glass plate. After cleaning the glass surface, the compressive stress value (CS Na ) and stress depth (DOL_ZERO Na ) was calculated. Here, DOL_ZERO Na is the depth at which the stress value becomes zero. In calculating the stress characteristics, the refractive index of each sample was set to 1.51 and the optical elastic constant was set to 30.1 [(nm / cm) / MPa].
[0114] As is clear from the table, when samples No. 1 to 35 and 38 to 215 were subjected to ion exchange treatment with KNO3 molten salt, the compressive stress value of the compressive stress layer on the outermost surface (CS K ) is 473MPa or more, and when ion-exchanged with NaNO3 molten salt, the compressive stress value of the outermost compressive stress layer (CS Na ) is 165 MPa or more, it is considered that ion exchange treatment is possible with any molten salt and that breakage is unlikely to occur when dropped. 3.74 On the other hand, sample No. 36 has a compressive stress value of CS Na ) is 163MPa, so it is considered to be easily broken when dropped. Sample No. 37 also has a liquidus viscosity of 10 3.5 Since the hardness is less than dPa·s, it is thought that it would be difficult to form into a plate.
[0115] As is clear from Tables 5 to 22, samples Nos. 37 to 215 have high acid resistance because ([SiO2]+1.2×[P2O5]-3×[Al2O3]-2×[Li2O]-1.5×[Na2O]-[K2O]-[B2O3]) is -36 mol % or more, and are therefore easily applicable to acid treatment processes and are considered suitable as cover glasses. EXAMPLES
[0116] First, glass raw materials were prepared so as to obtain the glass compositions of Sample No. 2 in Table 1 and Sample No. 35 in Table 4, and melted at 1600°C for 21 hours using a platinum pot. The obtained molten glass was then poured onto a carbon plate and formed into a flat plate shape, and cooled at 3°C / min in the temperature range between the annealing point and the strain point to obtain a glass plate (glass plate to be strengthened). The surfaces of the obtained glass plates were optically polished so that No. 2 had a plate thickness of 0.7 mm, and No. 35 had a plate thickness of 0.8 mm.
[0117] The obtained tempered glass plate was immersed in a molten salt of NaNO3 (NaNO3 concentration 100 mass%) at 380°C for 3 hours to perform an ion exchange treatment, and then immersed in a mixed molten salt of KNO3 and LiNO3 (LiNO3 concentration 2.5 mass%) at 380°C to perform an ion exchange treatment for 75 minutes. Furthermore, after cleaning the surface of the obtained tempered glass plate, the stress profile of the tempered glass plate was measured using a scattered light photoelastic stress meter SLP-1000 (manufactured by Orihara Seisakusho Co., Ltd.) and a surface stress meter FSM-6000 (manufactured by Orihara Seisakusho Co., Ltd.). In both cases, a non-monotonic stress profile similar to that in FIG. 1, that is, a stress profile having a first peak, a second peak, a first bottom, and a second bottom, was obtained. EXAMPLES
[0118] First, glass raw materials were prepared so as to obtain the glass compositions of Sample No. 109 in Table 12 and Sample No. 146 in Table 15, and melted at 1600°C for 21 hours using a platinum pot. The resulting molten glass was then poured onto a carbon plate and molded into a flat plate shape, and cooled at 3°C / min in the temperature range between the annealing point and the strain point to obtain a glass plate (glass plate to be strengthened). The surface of the resulting glass plate was optically polished to a plate thickness of 0.7 mm.
[0119] The obtained tempered glass plate was immersed in a molten salt of NaNO3 at 380°C (NaNO3 concentration 100% by mass) for 3 hours to perform an ion exchange treatment, and then immersed in a mixed molten salt of KNO3 and LiNO3 at 380°C (LiNO3 concentration 1.5% by mass) to perform an ion exchange treatment for 45 minutes. Furthermore, after cleaning the surface of the obtained tempered glass plate, the stress profile of the tempered glass plate was measured using a scattered light photoelastic stress meter SLP-1000 (manufactured by Orihara Seisakusho Co., Ltd.) and a surface stress meter FSM-6000 (manufactured by Orihara Seisakusho Co., Ltd.). As a result, a non-monotonic stress profile similar to that shown in Figure 2, that is, a stress profile having a first peak, a second peak, a first bottom, and a second bottom, was obtained. Therefore, it is expected that the obtained tempered glass plate has a low probability of breakage when dropped. EXAMPLES
[0120] First, glass raw materials were mixed to obtain the glass composition of sample No. 147 in Table 15, and melted at 1600°C for 21 hours using a platinum pot. The resulting molten glass was then poured onto a carbon plate and molded into a flat plate shape, and cooled at 3°C / min in the temperature range between the annealing point and the strain point to obtain a glass plate (glass plate to be strengthened). The surface of the resulting glass plate was optically polished to a plate thickness of 0.7 mm.
[0121] The obtained tempered glass plate was immersed in a molten salt of NaNO3 at 380°C (NaNO3 concentration 100% by mass) for 3 hours to perform an ion exchange treatment, and then immersed in a mixed molten salt of KNO3 and LiNO3 at 380°C (LiNO3 concentration 1.5% by mass) to perform an ion exchange treatment for 45 minutes. Furthermore, after cleaning the surface of the obtained tempered glass plate, the stress profile of the tempered glass plate was measured using a scattered light photoelastic stress meter SLP-1000 (manufactured by Orihara Seisakusho Co., Ltd.) and a surface stress meter FSM-6000 (manufactured by Orihara Seisakusho Co., Ltd.). As a result, a non-monotonic stress profile similar to that shown in Figure 2, that is, a stress profile having a first peak, a second peak, a first bottom, and a second bottom, was obtained. Therefore, it is expected that the obtained tempered glass plate has a low probability of breakage when dropped. [Industrial Applicability]
[0122] The tempered glass sheet of the present invention is suitable as a cover glass for touch panel displays of mobile phones, digital cameras, PDAs (personal digital assistants), etc. In addition to these applications, the tempered glass sheet of the present invention is expected to be used in applications requiring high mechanical strength, such as window glass, magnetic disk substrates, flat panel display substrates, flexible display substrates, solar cell cover glass, solid-state imaging device cover glass, and vehicle-mounted cover glass.
Claims
1. In the tempered glass having a compressive stress layer on the surface, the glass composition is, in mol%, SiO 2 50-80%, Al 2 O 3 17-25%, B 2 O 3 0.1-3.8%, Li 2 O 3-9.9%, Na 2 O 3-21%, K 2 O 0-10%, MgO 0.1-10%, ZnO 0-10%, P 2 O 5 0-1.97%, ZrO 2 0 to 1%, ([Li 2 O] + [Na 2 O] + [K 2 O]) in an amount of 23 mol % or less, Furthermore, Fe 2 O 3 Contains 0.001 to 0.1 mol % of [SiO 2 ]+1.2×[P 2 O 5 ]−3×[Al 2 O 3 ]−2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]-[B 2 O 3 ]≦−9.26 mol %.
2. Molar ratio ([Na 2 O]-[Li 2 O]) / ([Al 2 O 3 ]+[B 2 O 3 ]+[P 2 O 5 2. The tempered glass sheet according to claim 1 , wherein the relationship of 0.29 or less is satisfied.
3. Molar ratio ([B 2 O 3 ]+[Na 2 O]-[P 2 O 5 ]) / ([Al 2 O 3 ]+[Li 2 3. The tempered glass sheet according to claim 1, wherein the relationship of [R(t) / R(t)]≧0.30 is satisfied.
4. ([Li 2 O] + [Na 2 O] + [K 2 O]) at 12 mol % or more, 2 ]+1.2×[P 2 O 5 ]−3×[Al 2 O 3 ]−2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]-[B 2 O 3 4. The tempered glass sheet according to claim 1, wherein the relationship of: ]≧−22 mol % is satisfied.
5. P 2 O 5 The tempered glass sheet according to any one of claims 1 to 4, characterized in that the content of is 0 to 0.47 mol%.
6. B 2 O 3 The tempered glass sheet according to any one of claims 1 to 5, characterized in that the content of is 0.1 to 2.9 mol%.
7. The tempered glass plate according to any one of claims 1 to 6, wherein a compressive stress value of an outermost surface of the compressive stress layer is 200 to 1000 MPa.
8. The tempered glass sheet according to any one of claims 1 to 7, characterized in that the compressive stress layer has a stress depth of 50 to 200 µm.
9. High temperature viscosity 10 2.5 The tempered glass sheet according to any one of claims 1 to 8, characterized in that the tempered glass sheet has a temperature at dPa·s of less than 1650°C.
10. The tempered glass sheet according to any one of claims 1 to 9, further comprising an overflow merging surface at a central portion in a thickness direction of the tempered glass sheet.
11. The tempered glass sheet according to any one of claims 1 to 10, which is used as a cover glass for a touch panel display.
12. In the tempered glass having a compressive stress layer on the surface, the glass composition is Al 2 O 3 17 mol % or more, P 2 O 5 1 mol% or more, ([Li 2 O] + [Na 2 O] + [K 2 O]) at 12 mol % or more, 2 ]+1.2×[P 2 O 5 ]−3×[Al 2 O 3 ]−2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]-[B 2 O 3 9. The tempered glass sheet according to claim 1, wherein the relationship of ≧−22 mol % is satisfied.
13. A 2 O 3 The tempered glass sheet according to any one of claims 1 to 12, characterized in that the content of is 16.5 to 20.5 mol%.
14. [SiO 2 ]+1.2×[P 2 O 5 ]−3×[Al 2 O 3 ]−2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]-[B 2 O 3 ] ≦-16.92 mol %. The tempered glass sheet according to any one of claims 1 to 13, wherein the relationship is satisfied.
15. SnO 2 The tempered glass sheet according to any one of claims 1 to 14, characterized in that the content of is 0.01 to 1 mol%.
16. The strengthened glass plate according to any one of claims 1 to 15, wherein a compressive stress value of an outermost surface of the compressive stress layer is 894 MPa or more.
17. The tempered glass sheet according to any one of claims 1 to 16, characterized in that the stress profile in the thickness direction has at least a first peak, a second peak, a first bottom, and a second bottom.
18. The glass composition is, in mol%, SiO 2 50-80%, Al 2 O 3 17-25%, B 2 O 3 0.1-3.8%, Li 2 O 3-9.9%, Na 2 O 3-21%, K 2 O 0-10%, MgO 0.1-10%, ZnO 0-10%, P 2 O 5 0-1.97%, ZrO 2 0 to 1%, ([Li 2 O] + [Na 2 O] + [K 2 O]) in an amount of 23 mol % or less, Furthermore, Fe 2 O 3 Contains 0.001 to 0.1 mol % of [SiO 2 ]+1.2×[P 2 O 5 ]−3×[Al 2 O 3 ]−2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]-[B 2 O 3 ]≦−9.26 mol %.
19. The glass composition is, in mol%, SiO 2 50-80%, Al 2 O 3 17-25%, B 2 O 3 0.1-3.8%, Li 2 O 3-9.9%, Na 2 O 3-21%, K 2 O 0-10%, MgO 0.1-10%, ZnO 0-10%, P 2 O 5 0-1.97%, ZrO 2 0 to 1%, ([Li 2 O] + [Na 2 O] + [K 2 O]) in an amount of 23 mol % or less, Furthermore, Fe 2 O 3 Contains 0.001 to 0.1 mol % of [SiO 2 ]+1.2×[P 2 O 5 ]−3×[Al 2 O 3 ]−2×[Li 2 O]-1.5×[Na 2 O]-[K 2 O]-[B 2 O 3 ]≦−9.26 mol %; and an ion exchange step of performing ion exchange treatment on the glass sheet to be tempered a plurality of times to obtain a tempered glass sheet having a compressive stress layer on a surface thereof.
Citation Information
Patent Citations
Matrix glass for cathode-ray tube panel, panel for cathode-ray tube and production method therefor
JP2003212591A
Glass member
JP2006083045A
Method for manufacturing glass substrate for data storage medium and glass substrate
JP2011123924A
Damage-resistant chemically strengthened protective cover glass
JP2011510903A
Scratch-resistant article maintaining optical properties
JP2016524581A